LEXICAL COLLOCATION AND TEXTUAL COHESION IN STUDENT’S ENGLISH WRITING DISCUSSION TEXT - putri Sundari Minang; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2022)
Abstract: The purpose of this study was to determine (1) the form of significant lexical collocation in student's English writing discussion text, (2) the process of lexical collocation creates cohesion in student's English writing discussion text, and (3) the cultural reflection displayed by the structure of lexical collocation and textual cohesion in student's English writing discussion text. This study applies a mixture of descriptive and quantitative qualitative methods in describing research findings. The data source of this research is the results of writing discussion texts in 3 PKBM Karawang. Data that has been documented in total is 30 discussion texts with 5274 words and 1664 types of words.  The author uses the help of a computer application called Antconc to obtain the collocation data. The findings show that (1) the lexical collocations produced by students in Paket C in the discussion text are L1 (15%), L2 (34%), L3 (18%), L4 (4%), L5 (18%), and L7 (11%); (2) reference data are personal (51%), demonstrative (30%), and comparative (10%); conjunction data are additive (44%), adversative (15%), temporal (5%), and causal (36%). (3) The cultural representation found was the issue raised as the title of the text sourced from daily activities and used the words claim and assumed to describe students' ideas and opinions in the text.  This shows that collocation is able to get a special place in learning English to improve the writing ability of students in Paket C in PKBM.